Employee acceptance towards implementation of RFID: a case of Pos Malaysia Berhad, Malaysia / Noor Atikah Mohd Tanzizi - Mohd Tanzizi, Noor Atikah (Faculty of Business and Management, 2013)
RFID technology is one of the technology solutions in supply chain management, retailing, medical, operation and services includes production industries. This study composes three (3) objectives which are to identify the relationship between perceived ease of use and perceived usefulness with intention to use RFID, to identify which factors are giving more influence towards intention to use RFID and to differentiate the demographic profile (age, working experience and etc.) employees in accepting the RFID. The basic Technology Acceptance Model (TAM) is used as a theoretical framework. The basic TAM is only perceived ease of use and perceived usefulness are influencing the acceptance of a new technology. This study is used census technique and the model is tested using instrument which is questionnaires that respond by the whole population with 236 respondents at Pos Malaysia Berhad, Malaysia. First objective showed that, those two (2) independent variables (perceived ease of use and perceived usefulness) have significant relationship towards intention to use RFID. Second objective exposed that perceived ease of use is the most important factor and followed by perceived usefulness. For the third objective, the result showed that there is no significant difference between age and working experience and there is significant difference between SPM and diploma towards intention to use RFID among postmen. Additionally, there is significant difference displayed in region towards intention to use RFID. The result of this study also indicates that, the result for two (2) independent variables with 81.5% are able to explain the relationship of intention to use RFID and it have any other factors for this study instead of perceived ease of use and perceived usefulness. Finally, from the result, Pos Malaysia Berhad has to generate some new ideas in order to increase the perceived ease of use and perceived usefulness. For example, by giving them good training, motivation and also user-friendly tools and equipment.